UPAYA MEMPERBAIKI EKONOMI BERAS DI PROVINSI NUSA TENGGARA TIMUR ANALISIS DATA SEKUNDER TAHUN 2003-2017) - Fransisca Erna Teda; Fredrik L Benu; Wiendiyati Wiendiyati (Undana Press, 2020)
The aim of this research were to review the state of rice industry over the past 15 years (2003-2017) based on the demand and supply situation in East Nusa Tenggara. The development of the price of rice, the factors that influence the demand and supply, and determine the policy impact of rice demand and supply in East Nusa Tenggara Province. This research uses the econometric model, that is a simultant structural equation,which was indentified by the order condition and it was approaches using Two Stage Least Square (2SLS). The data used in this research was the time series of secondary data during 15 years period from 2003-2017 that was provided by Central Startics Office, the National Logistics Authority, the NTT Agricultural Bureau and other publications related to this investigation. The analysis showed that the amount of rice production was really depended on harvest area, rice consumption, rice supply and rice production in the previous year. The retail price of rice was responded to the price of corn and the demand for rice in the long term, while in the short term it only responded to the price of corn. The amount of rice consumption responded to rice production, rice prices and rice demand. Rice imports reacted to rice production, rice prices, corn prices and rice consumption in the long run. Based on the results of the research, it was suggested that the area of irrigation needs to be extended,in each region of East Nusa tenggara Province, particularly technical irrigation in order to increase the rice production, and it es neededto do diversification programs in order to reduce dependency rice. The weakness of this research was it used the inpure simultan model.